2012
DOI: 10.1152/ajpheart.00512.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increases in intracellular sodium activate transcription and gene expression via the salt-inducible kinase 1 network in an atrial myocyte cell line

Abstract: Popov S, Venetsanou K, Chedrese PJ, Pinto V, Takemori H, Franco-Cereceda A, Eriksson P, Mochizuki N, Soares-da-Silva P, Bertorello AM. Increases in intracellular sodium activate transcription and gene expression via the salt-inducible kinase 1 network in an atrial myocyte cell line. Am J Physiol Heart Circ Physiol 303: H57-H65, 2012. First published March 30, 2012 doi:10.1152/ajpheart.00512.2011.-Cardiac hypertrophy (CH) generally occurs as the result of the sustained mechanical stress caused by elevated syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…SIK1 was initially discovered in adrenal glands of rats fed with a HS diet and it has been shown to act as a mediator during the cellular adaptation to variations in intracellular sodium in a variety of cell types. 4,6 In agreement with previous literature, we observed that the regulatory action of SIK1 on blood pressure levels is exerted specifically during abnormal salt intake. Furthermore, our results showed that within the vasculature SIK1 was induced in the VSMCs layer of the wild-type mice aorta in response to the chronic HS intake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SIK1 was initially discovered in adrenal glands of rats fed with a HS diet and it has been shown to act as a mediator during the cellular adaptation to variations in intracellular sodium in a variety of cell types. 4,6 In agreement with previous literature, we observed that the regulatory action of SIK1 on blood pressure levels is exerted specifically during abnormal salt intake. Furthermore, our results showed that within the vasculature SIK1 was induced in the VSMCs layer of the wild-type mice aorta in response to the chronic HS intake.…”
Section: Discussionsupporting
confidence: 92%
“…3 In addition, SIK1 regulates active sodium transport in renal and lung epithelia by increasing sodium-potassium ATPase (Na + ,K + -ATPase) activity and mediates gene expression activation in cardiac myocytes on increase in intracellular sodium. [4][5][6] SIK1 is also present in the vasculature and its activity in endothelial and vascular smooth muscle cells (VSMCs) seems to be relevant for controlling the vascular tone and arterial blood pressure by regulating Na + ,K + -ATPase activity in VSMCs. 7 A polymorphism in SIK1 gene resulting in 1 amino acid change ( 15 Gly→Ser) in the protein enhances the kinase activity and is associated with lower blood pressure and reduced left ventricle (LV) mass index in humans.…”
mentioning
confidence: 99%
“…Although ubiquitous, this effect is particularly relevant in the renal epithelia [15], and in cardiac myocytes [33]. In cardiac myocytes, SIK1 mediates the increases in MEF2C, NFAT5c and genes associated with CH in response to increases in intracellular sodium [33].…”
Section: Discussionmentioning
confidence: 99%
“…PKC-related kinases 1 and 2 (PRK1 and PRK2) also target T292 (68), highlighting the PKC signaling pathway as an important determinant of HDAC5 phosphorylation status. Other enzymes that target both S259 and S498 are AMP-activated protein kinase (69,70), G protein-coupled receptor kinase-5 (GRK5) (71), whereas salt-inducible kinase 1 (SIK1) phosphorylates only S259 (72).…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%
“…Independently of blood pressure, high salt intake has also been known to be associated with left ventricle hypertrophy (128,144). More recently, this mechanism was shown to be phosphorylation-dependent, as increased sodium levels activate the critical cardiac kinase SIK1, leading to HDAC5 phosphorylation and enhanced MEF2 and NFAT transcriptional activity (72). Interestingly, a recent study examined the mechanisms through which clinically relevant neurohormonal stimuli regulate HDAC phosphorylation in adult cardiomyocytes (62).…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%